2020
DOI: 10.1186/s12877-020-1502-7
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment for community-based, person-centered care for older adults

Abstract: Background: Many health and social needs can be assessed and met in community settings, where lower-cost, person-centered, preventative and proactive services predominate. This study reports on the development and implementation of a person-centered care model integrating dental, social, and health services for low-income older adults at a community dental clinic co-located within a senior wellness center. Methods: A digital comprehensive geriatric assessment (CGA) and referral system linking medical, dental, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…36 However, CGAs concentrate primarily on medical context and unfortunately do not include oral health measures and components. 14 Even though previous studies have demonstrated the benefits of integrating oral health screening with general health screening for older adults. [37][38][39] This is might be hard to implement due to lack of dental staff and limited recourses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…36 However, CGAs concentrate primarily on medical context and unfortunately do not include oral health measures and components. 14 Even though previous studies have demonstrated the benefits of integrating oral health screening with general health screening for older adults. [37][38][39] This is might be hard to implement due to lack of dental staff and limited recourses.…”
Section: Discussionmentioning
confidence: 99%
“…The CGAs concentrate on the whole person approach and evaluate multiple components of older adults’ general health, which allows a comprehensive judgement on the overall health and the complex needs of older adults 36 . However, CGAs concentrate primarily on medical context and unfortunately do not include oral health measures and components 14 . Even though previous studies have demonstrated the benefits of integrating oral health screening with general health screening for older adults 37‐39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive effects of CGA include slowing down functional decline and reduction of hospitalisations and admissions to nursing homes [ 15 , 16 ]. CGA has been modified and adapted to various settings; a wide range of CGAs using different instruments with different intensity has been studied in primary care [ 14 , 16 18 ]. In spite of a great number of intervention studies, there is insufficient evidence for effectiveness of CGA in primary care regarding reduced mortality or inpatient care [ 11 , 17 ].…”
Section: Introductionmentioning
confidence: 99%